A RESOLUSI KENAKALAN REMAJA OLEH GURU PAI DI SMPN 3 SATU ATAP NGORO MOJOKERTO: RESOLUSI KENAKALAN REMAJA OLEH GURU PAI DI SMPN 3 SATU ATAP NGORO MOJOKERTO - Ulfatonah, Nida; Inayatul Ilahiyah, Iva; Masruroh, Laily (PAI FAI UNHASY Tebuireng Jombang, 2024)
Abstract: An activity that shows that laws and norms are violated, then this is within the scope of juvenile delinquency. The existence of constraints on the distance between schools and educational buildings is also one of the triggering factors. The researcher chose the title above with the aim of clarifying juvenile delinquency at SMPN 3 Satu Atap Ngoro?, resolution of juvenile delinquency with the efforts made by PAI teachers, as well as supporting and inhibiting factors for this research problem. The research carried out chose qualitative as the easiest technique and case studies were the type that had been chosen. This study resulted in a new phenomenon, namely the resolution carried out by PAI teachers in terms of juvenile delinquency by means of prevention (preventive), healing (curative) and coaching. Prevention (preventive) is carried out with counseling which is conceptualized into learning activities, there are lots of misbehaviors committed by students, but these delinquencies can still be said to be mild, one of the inhibiting factors for the resolution of juvenile delinquency is that society there does not allow their children to go to school when they have to help both people his parents.